'More than Words': touch practices in child and family social work - Lynch, Rachel; Garrett, Paul Michael (Child & family social work, 2010)
ABSTRACT This paper explored the subject of physical touch occurring between social workers and children in the Republic of Ireland. Here, it was maintained that touch practices occupy an ambiguous area for social work practitioners. The empirical component was based on interviews that were conducted with a small group of practitioners in one particular Irish county. The study provided insight into the social workers' personal experiences of, and opinions on, touch with children in the context of their practice. Despite a lack of prescriptive ‘do's and don'ts’ regarding physical touch and social work, the findings suggested that social workers do not consciously engage in physical touch with children. Rather, touch occurs as a result of practicality and safety concerns for a child. Recognized as beneficial in terms of communication, reassurance and conveying empathy, touch practices are also guided by a fear of misinterpretation, allegations and concern for causing harm to the child. The place of physical touch with children is regarded as being outside the remit of the social work role. Despite this, a majority of those interviewed spoke of a desire to have more discussion and guidance on the subject of physical touch with children within their work locations.